Stress-induced obesity in mice causes cognitive decline associated with inhibition of hippocampal neurogenesis and dysfunctional gut microbiota - Liu, Yu-e; Zhao, Zhihuang; He, Haili; Li, Liangyuan; Xiao, Chenghong; Zhou, Tao; You, Zili; Zhang, Jinqiang (Frontiers in Microbiology, 2024)
1. Chronic stress can induce diet-independent obesity in mice.2. Stress-induced obesity involves alterations in the gut microbiome and hyperactivation of the hypothalamic-pituitary-adrenal axis.In brief: Liu et al. provide evidence from a mouse model that chronic stress can induce dietindependent obesity and cognitive deficits involving hyperactive hypothalamic-pituitary-adrenal signaling, hyperactive microglia, impaired neurogenesis, systemic inflammation, and alterations in the gut microbiome. Mitigating one or more of these processes may ameliorate the stress-induced 2 cognitive deficits and obesity.